Phenology and maturation of ’Cabernet Franc’ grapevine due to different retained nodes number in high altitude region of Santa Catarina State - Würz, Douglas André; Bonin, Bruno Farias; Brighenti, Alberto Fontanella; Canossa, Adrielen Tamiris; Reinehr, Juliana; Allebrandt, Ricardo; de Bem, Betina Pereira; Rufato, Leo; Kretzschmar, Aike Anneliese (Revista de Ciências Agroveterinárias, 2019)
The objective of this work is to evaluate the effect of load of buds on phenology and the technological and phenological maturation of Cabernet Franc grapevine in high-altitude region of Santa Catarina. The present work was conducted during the 2016/2017 harvest, in a commercial vineyard, located in the city of São Joaquim. The treatments consisted of four different levels of bud loads: 15, 30, 50, and 75 plant-1 buds. During the vegetative cycle of the grapevine, the main phenological stages were evaluated (budding, flowering, color turning, and maturation for harvest), being evaluated qualitatively and qualitatively. At the time of harvest, 100 berries were collected per plot to determine technological and phenolic maturation. The experimental design was a randomized block design with four blocks and five plants per plot. The data were submitted to analysis of variance (ANOVA) and compared by Tukey test with a 5% probability of error. The increase of the bud load resulted in a longer duration of Budding and Flowering, whereas for the duration of Verásion, no effect of different bud loads was observed. Technological maturation was not influenced by the increase of the yolk load, and in the sample loading intervals (15 to 75 yolks/plant), maturation rates considered adequate for the elaboration of quality wines were obtained. The increase of the yolk load did not give a significant difference in the physical-chemical attributes, in the phenolic composition and color of the berries.